FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN TERKAIT KEPUTIHAN PADA SISWI SMP NEGERI 214 JAKARTA TAHUN 2020 - Diyas Mellya Octaviani (2021)
Every year as many as 5% of adolescents in the world suffer from sexually transmitted diseases (STDs) with symptoms of vaginal discharge. Several internal factors (age) and external factors (parents 'work, parents' income, sources of information, family support and health services) can influence adolescent knowledge regarding vaginal discharge. This research was conducted on students at SMP Negeri 214 Jakarta. The purpose of this study is to find out what are the internal factors and external factors related to knowledge. The number of samples in this study were 226 students and used a cross sectional study design. The statistical test used is the Chi-Square test with a significance level of 0.05. Based on the results of this study, it shows that the respondents have poor knowledge regarding vaginal discharge. The results of this study indicate that there is a significant relationship between internal factors (age) and external factors (sources of information, family support, and health services) and knowledge related to vaginal discharge. Meanwhile, the variables that do not have a significant relationship are external factors (parents 'work and parents' income). Suggestions for parents to give more attention and accurate information about vaginal discharge. Principals and teachers can conduct counseling and counseling activities on reproductive health, especially regarding vaginal discharge as a promotional effort to improve community health status. Keywords: Student, Leucorrhoea, Knowledge